Speed of information processing in children referred for learning problems: performance on a visual filtering test. - Weiler MD; Harris NS; Marcus DJ; Bellinger D; Kosslyn SM; Waber DP (Journal of Learning Disabilities)
Children referred for evaluation of learning impairment (LI, N =100) and a comparison group of nonreferred (NLI, N = 243) children were evaluated on a visual filtering task. The task was designed hierarchically to provide for evaluation of component operations-serial search, parallel search, decision, and response. With each additional processing demand, response times increased disproportionately for the LI group relative to the NLI group. Overall response time reliably predicted academic skills and cognitive ability, but was more strongly related to group membership. Thus, this nonverbal visual task is sensitive to a characteristic of children with learning problems over and above discrete academic and cognitive skills. Children with problems adapting to the demands of schooling may be distinguished by a disproportionate vulnerability to processing load.